PENGARUH KEPEMILIKAN MANAJERIAL, TINGKAT HUTANG DAN GROWTH OPPORTUNITIES TERHADAP KONSERVATISME AKUNTANSI - Ruth Novitaria Wiguna, Rini Tri Hastuti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to find out the effect of managerial ownership, leverage and growth opportunities to accounting conservatism. The population of this study is manufaktur companies that listed on Indonesia Stock Exchange for the periode 2015-2018. Data collected by purposive sampling method and the sample amounted to 56 companies. This study used multiple regression as techniques for data analysis and helped by Eviews verse 10.0 and Microsoft Excel 2013. The result of this study indicate that the negative impact of leverage on accounting conservatism, while managerial ownership and growth opportunities have no significant effect on accounting conservatism. However, this study shows that simultaneously managerial ownership, leverage, and growth opportunities have a significant effect on accounting conservatism.